A Change Point Method for Monitoring Generalized Linear Profiles in Phase I. (25th June 2014) - Shadman, Alireza; Mahlooji, Hashem; Yeh, Arthur B.; Zou, Changliang
Abstract : The Phase I applications of the statistical profile monitoring have recently been extended to the case when the response variable is binary. We are motivated to undertake the current research in an attempt to try to provide a unified framework for the Phase I control in the context of statistical profile monitoring that can be used to tackle a large class of response variables, such as continuous, count, or categorical response variables. The unified framework is essentially based on applying the change point model to the class of generalized linear models. The proposed Phase I control chart is assessed and compared with the existing charts under binomial and Poisson profiles. Some diagnostic procedures are also discussed. A real data set obtained from a test lab concerning the dispersion of carbon black filler in a rubber mix is used to demonstrate how the proposed chart can be used in practical applications. Some future research directions are also discussed. Copyright © 2014 John Wiley & Sons, Ltd.